2017
DOI: 10.1002/smll.201701808
|View full text |Cite
|
Sign up to set email alerts
|

Memantine‐Loaded PEGylated Biodegradable Nanoparticles for the Treatment of Glaucoma

Abstract: Glaucoma is a multifactorial neurodegenerative disease associated with retinal ganglion cells (RGC) loss. Increasing reports of similarities in glaucoma and other neurodegenerative conditions have led to speculation that therapies for brain neurodegenerative disorders may also have potential as glaucoma therapies. Memantine is an N-methyl-d-aspartate (NMDA) antagonist approved for Alzheimer's disease treatment. Glutamate-induced excitotoxicity is implicated in glaucoma and NMDA receptor antagonism is advocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 70 publications
(115 reference statements)
4
56
0
1
Order By: Relevance
“…This cell loss is dependent on the inoculated dose of NMDA, since, while a dose of 10 nmol did not cause any cell loss, the intraocular injection of 160 nmol may have induced a cell loss of ca. 70% [6], resembling these models to those obtained by crushing the optic nerve [14,15].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This cell loss is dependent on the inoculated dose of NMDA, since, while a dose of 10 nmol did not cause any cell loss, the intraocular injection of 160 nmol may have induced a cell loss of ca. 70% [6], resembling these models to those obtained by crushing the optic nerve [14,15].…”
Section: Introductionsupporting
confidence: 71%
“…It has been reported that the loss of RGCs, or just their functional lesion, may affect the transmission of the light signal to higher centers of the visual pathway. Frequently, the administration of glutamate receptor antagonists provides protection of these retinal cells, suggesting that a toxic effect of glutamate triggered by different etiologies might be involved [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Instilled in the conjunctival sac of the eye was 50 µL of sample and the appearance of irritation was observed at the time of administration and after 1 h. The evaluation was undertaken by direct observation of the anterior segment of the eye calculating the injuries of the conjunctiva, iris and cornea. The punctuation applied has been described elsewhere [20] and the ocular irritation index has been calculated according to Equation (3). Langmuir monolayers were obtained by spreading a lipid solution at the air/water interface.…”
Section: In Vivo Ocular Irritation Assaymentioning
confidence: 99%
“…Polymeric nanoparticles can be obtained from natural, semi-synthetic or synthetic polymers (e.g., chitosan [37][38][39], polylactic acid (PLA), poly(lactic-co-glycolic acid) (PLGA) [40][41][42][43]), which will then govern the way the drugs are encapsulated inside the matrix (dissolved or dispersed) or attached onto the nanoparticle' surface (chemically bound or adsorbed), and how the drug is released [44]. Polymeric nanoparticles can be produced with a variety of sizes and shapes, with high drug payload for both hydrophilic and lipophilic molecules, can be surface-modified to increase the plasma half-life (e.g., PEGylation [45,46]) to have site-specific targeted delivery [47], and release the drug in a controlled fashion [48][49][50].…”
Section: Production Methods Of Clinically Compliant Nanopharmaceuticsmentioning
confidence: 99%